Decentralisation without decentralisation: Bangladesh's failed attempt to transfer power from the central government to local governments. Issue 3 (3rd July 2017) - Panday, Pranab
Abstract : This article addresses decentralising initiatives in Bangladesh with reference, first, to significant literature on decentralisation in the context of development and, thereafter, to a particular reform involving the introduction of the Upazila Parishad (UZP) as a potentially important tier of local government. While the reform heralded a possible expansion of local participation and the taking of responsive local action, the functioning of the UZP has not lived up to the promises and expectations. A lack of a proper transfer of power and responsibility to the elected representatives, the existence of centrally-controlled administration and planning, and the extensive interference of politicians and bureaucrats has limited considerably the capacity of the UZP to operate effectively. Only through a reduction of central control and a recasting of local action will it be able to achieve its significant goals and objectives as a vital form of local government and governance.